Multiple infections with hepatitis A virus and development of rheumatoid arthritis among waste water treatment plant workers - Dina Nadeem Abd-Elshafy; Hala Zaki Raslan; Rola Nadeem; Mona Abd-ElKader Awad; Said Shalaby; Mahmoud Mohamed Bahgat (Journal of Infection in Developing Countries)
Introduction: In the present work, we studied the association between multiple exposure of waste water treatment plant workers to infection with existing hepatitis A virus in waste water and development of rheumatoid arthritis, taking in consideration number of working years as an indicator for frequency of exposure to infection, compared to non waste water treatment plant workers.